Legume integration in smallholder farming systems for food security and resilience to climate change - Meseretu Melese; Bereket Getachew; Endalkachew Woldemeskel; Ashenafi Hailu Gunnabo (PLoS ONE, 2025)
A random sample of 847 households (HHs) in southern Ethiopia was used to assess the impact of HH characteristics, land and livestock ownership, seasonal variations, and agricultural challenges on cereals and legumes, crucial to community livelihoods. A structured survey was integrated into the ODK data collection tool, validated, and used with trained agricultural agents, and analyzed using an R statistical package. Farm productivity was significantly influenced by gender, since male headed HHs produced 25.5% more yield than female headed HHs. Livestock ownership, land cultivation, farm productivity and product utilizations were also varied among the HHs. Furthermore, agricultural practices like labor utilization, fertilizer and composite application, and use of improved seed varieties significantly affected the farm productivity. Besides, maize was identified as the principal and top-priority crop, while common bean (legume) was the second-priority crop for local people. This shows that legumes were important in the region’s agricultural systems, but some farmers experienced reduced productivity due to poor agronomic practices. Consequently, a substantial proportion of farmers (>50%) faced food shortages from February to June, representing the peak of the dry season and the beginning of the rainy season (April to May). Integrating early-maturing legumes in the farming system would help to escape the food shortage periods. Many farmers disclosed that the cost of chemical fertilizers’ was unaffordable, indicating a need for options like use of rhizobia inoculants and showed interest to use on their farms for improved productivities.